1986
DOI: 10.1042/cs0710573
|View full text |Cite
|
Sign up to set email alerts
|

Compensatory spleen growth and protective function in rats

Abstract: 1. To quantify compensatory spleen growth after reduction in splenic mass and to determine the effect of age and vascular supply on remnant growth, we examined adult and weanling rats for remnant regeneration and adult rats for host protection against bloodstream pneumococcal challenge at intervals up to 180 days after partial resection or autograft implantation. 2. In adults, subtotally resected spleens with remnant blood flow and segmental anatomy otherwise intact (eutopic remnants) displayed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

1987
1987
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Splenosis was once thought to protect splenectomised trauma patients from subsequent OPSI (15). This proved untrue, as adequate splenic function occurs only in the presence of at least 30°/o of original splenic mass witha normal or near normal blood supply (2,8,20).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Splenosis was once thought to protect splenectomised trauma patients from subsequent OPSI (15). This proved untrue, as adequate splenic function occurs only in the presence of at least 30°/o of original splenic mass witha normal or near normal blood supply (2,8,20).…”
Section: Discussionmentioning
confidence: 99%
“…In order to prevent unnecessary surgery in this group of patients, we recommend the use of the open abdominal tap. This technique has been shown to be rcliable and relatively safe (20). Since blood in the peritoneal cavity in this setting is an expected finding, a peritoneal tap consisting of elevated diastase levels or bacterja seen on gram stain of spun collected fluid indicates gastrointestinal o r pancreatic trauma.…”
Section: Discussionmentioning
confidence: 99%
“…(17,18) Van Wyck et al, have reported that preservation of a splenic remnant, approximately one-third the size of the normal spleen, seems critical to maintaining this protective effect in the rat. (19)(20)(21) Several authors have confirmed the effectiveness of partial splenectomy in the treatment of children with mild to moderate HS, reserving total splenectomy for severe disease. (14) Partial splenectomy is a viable option for selected patients with HS leading to improvement in hematologic and clinical abnormalities.…”
Section: Discussionmentioning
confidence: 99%
“…The regeneration of splenie tissue after autotransplantation or splenic artery ligation in patients and in animal models is well described, but the capacity of such tissue to proteet against OPSI is controversial, some authors reporting benefit, others no improvement [8,9,[12][13][14][15][16][17], The spleen has two major functions in resistance to infection, the synthesis of specific opsonins or antibodies, and the clearance of poorly opsonized baeteria from the circulation. We have shown that antibody synthesis in humans and rats with regenerated splenic tissue is impaired [18,19], although significant and perhaps protective serum concentrations can be achieved by immunization.…”
Section: Discussionmentioning
confidence: 99%